The Candida albicans Na(+)/H(+) antiporter exports potassium and rubidium - Kinclová, O; Potier, S; Sychrová, H (FEBS letters, 2001)
The Candida albicans Cnh1p belongs to the family of Na(+)/H(+) antiporters (TC 2.A.36) but it transports besides toxic sodium and lithium also rubidium and potassium. Upon heterologous expression in a Saccharomyces cerevisiae salt-sensitive strain, the Cnh1p is targeted to the plasma membrane and its transport activity results in increased tolerance of cells to external alkali metal cations. The cation efflux activity of Cnh1p in S. cerevisiae depends on the gradient of protons across the plasma membrane, and a Cnh1p-mediated K(+) efflux is involved in a cell response to sudden rise of cytoplasmic pH.
Keywords: Molecular Sequence Data; Saccharomyces cerevisiae; Potassium; sekvence aminokyselin; iontový transport; Na(+)-H(+) antiport; substrátová specifita; draslík; DNA fungální; Candida albicans; fungální proteiny; Cloning, Molecular; Ion Transport; Rubidium; Base Sequence; sekvence nukleotidů; Fungal Proteins; Sodium-Hydrogen Exchangers; Amino Acid Sequence; rubidium; DNA, Fungal; Substrate Specificity; klonování DNA; molekulární sekvence - údaje